Experimental investigation of a multistage evacuated solar still - Abakrb, Yousif A.; Ismail, Ahmad Faris; Ahmed, Mirghani Ishak (IIUM Press, 2011)
A new concept of a multistage evacuated solar still was developed; a full size prototype was constructed and tested. The amounts or condensate produced generated from each stage was collected separately and measured frequently. The overall results showed that the productivity of the new concept is highly better under the cloudy low solar radiation conditions.